2001
DOI: 10.1021/ie0009379
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Mass Transfer and Reaction in Coking of Thin Films of an Athabasca Vacuum Residue

Abstract: The coupling of reaction and mass transfer was investigated for the thermal cracking of thin films of an Athabasca vacuum residue. Thin films of the vacuum residue were coated on the interior of a stainless steel tube and then heated to 530 °C using induction heating. Vapor products were swept out of the reaction zone with nitrogen, and reactions in the liquid phase were allowed to proceed to completion. Coke yield, total liquid product, and gas make were determined for initial film thicknesses ranging from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 10 publications
4
69
0
Order By: Relevance
“…They also observed a dependence of coke yield on the thickness of the reacting film, which suggests a coupling of mass transfer and reaction during the cracking reactions. Gray et al (2001) confirmed the importance of film thickness in coking by demonstrating the dependence of both the mode of product transport and the yield of coke on film thickness. In the range from 20-80 pm liquid film thickness at 530°C, the product evolution shifted from passive diffusion through the liquid to active bubbling.…”
mentioning
confidence: 57%
“…They also observed a dependence of coke yield on the thickness of the reacting film, which suggests a coupling of mass transfer and reaction during the cracking reactions. Gray et al (2001) confirmed the importance of film thickness in coking by demonstrating the dependence of both the mode of product transport and the yield of coke on film thickness. In the range from 20-80 pm liquid film thickness at 530°C, the product evolution shifted from passive diffusion through the liquid to active bubbling.…”
mentioning
confidence: 57%
“…An oil film is formed on the hot coke particles and cracks into various volatile product fractions. It has been found that the thickness of the films impacts the yield of coke, with thicker films yielding more coke than thinner films [4,5]. Hence, controlling the size of droplets exiting the nozzle may be an important goal in further optimizing the fluid coking process.…”
Section: Introductionmentioning
confidence: 99%
“…In most processes, slugging is not desirable and should be avoided. It is also necessary to point out that the high jet flow rates tend to increase solids elutriation, which may lead to low reaction efficiency, high catalyst cost (Gray et al, 2001). In brief, the jet gas flow rate should be selected carefully, especially for small-scale fluidized bed reactors.…”
Section: Voidage Profilesmentioning
confidence: 99%